Oral Azacitidine (CC-486) for the Treatment of Myelodysplastic Syndromes and Acute Myeloid Leukemia. (13th October 2015) - Cogle, Christopher R.; Scott, Bart L.; Boyd, Thomas; Garcia-Manero, Guillermo
Abstract: : The myelodysplastic syndromes (MDS) comprise a heterogeneous group of clonal myeloid malignancies characterized by multilineage cytopenias, recurrent cytogenetic abnormalities, and risk of progression to acute myeloid leukemia (AML). AML, which can occur de novo as well as secondary to MDS, is characterized by malignant clones of myeloid lineage in the bone marrow and peripheral blood, with dissemination into tissues. The cytidine nucleoside analog and epigenetic modifier azacitidine is approved in the U.S. for the treatment of all French-American-British subtypes of MDS and in many countries for the treatment of AML with 20%–30% blasts and multilineage dysplasia according to the World Health Organization classification. Benefits of azacitidine treatment of patients with AML with >30% blasts have also been shown in a recent phase III trial. Oral administration of azacitidine may enhance patient convenience, eliminate injection-site reactions, allow for alternative dosing and scheduling, and enable long-term treatment. Phase I studies with oral azacitidine (CC-486) have shown biological activity, clinical responses, and tolerability in patients with MDS and AML. Extended dosing schedules of oral azacitidine (for 14 or 21 days of 28-day cycles) are currently under investigation as frontline therapy in patients with lower risk MDS, as maintenance therapy for patients with AML not eligible for stem cell transplant, and as maintenance therapy for patients with MDS or AML following stem cell transplant. This review presents clinical data supporting the use of injectable azacitidine in MDS and AML and examines the rationale for and results of the clinical development of oral azacitidine. Abstract : This review presents clinical data supporting the use of injectable azacitidine in myelodysplastic syndromes and acute myeloid leukemia and examines the rationale for and results of the clinical development of oral azacitidine.